Avaliacao das influencias litologicas e topograficas na classificacao de bacias hidrograficas. - Cesar, A. L. (My University, 1982)
Morphometric variables such as drainage density, hydrographic density and topographic texture have been successfully used to describe hydrographic basins. This paper deals with possible relationships among those morphological variables and lithological and altimetric aspects, in order to find a classification of several geographical areas in the state of Sao Paulo, Brazil.-from English summary
The evaluation of topographical and lithological influences in the classification of drainage basins, Sao Paulo, Brazil
Keywords: Hydrographic basins; nvironmental characters.